Structures of Some Mercury Compounds in Low Oxidation States - Tun, Zin (My University, 1984)
Structures of Hg compounds in fractional oxidation states lower than +1, Hg₃-δMF₆ (M = Sb, Nb, Ta), Hg₃MF₆ (M = Nb, Ta), Hg₄(Ta₂F₁₁)₂ and Hg₃(NbF₅)₂SO₄, were determined at room temperature and at lower temperatures using X ray and neutron diffraction. The Hg₃-δMF₆ compounds, isostructural with Hg₃-δAsF₆, contain infinite chains of Hg which are incommensurate and thus disorder with the MF₆ host lattice. A comparison between the structures showed that the differences observed in the parameters of the chain compounds are completely accounted for by the difference in anion size. The chain-host lattice incommensurability also results in disorder among the chains at room temperature but an ordering develops at lower temperatures. As in Hg₃-δAsF₆, short and long range order phases were observed in experiments with Hg₃-δSbF₆ and Hg₃-δTaF₆. The characteristics of the short range order phase are different in each compound indicating that the details of chain-chain interactions are not the same. Emery-Axe order parameter theory which predicts the development of long range order phase was tested for M = As, Sb, Ta but agreement was obtained only for Hg₃-δSbF₆.
A structure consisting of hexagonal closed-packed layers of Hg atoms was proposed for the Hg₃MF₆ compounds. The unusual 2-dimensional Hg-Hg bonding of these compounds represents an intermediate stage between the elemental solid Hg and the Hg₃-δMF₆ compounds which form 3- and 1-dimensional Hg-Hg bonds respectively.
The Hg₄(Ta₂F₁₁)₂ and Hg₃(NbF₅)₂SO₄ consists of finite polyatomic Hg ions. The former shows a tendency of cations to link into infinite zigzag chains, a feature also seen in Hg₄(AsF₆)₂, while the latter does not show such a tendency.
Keywords: Chemistry; Chemistry